EXPERIMENTAL STUDY OF THE VENTILATION OF STOCKED WHEAT IN A SILO - Hussine, A; Bettahar, A; Youcefi, A (university of el oued/جامعة الوادي, 2018)
This work is an experimental study of the ventilation of durum wheat stored in a silo of reduced dimensions and equipped with a ventilation system. The wheat, freshly harvested in June of the year 2015, was put in the silo. It underwent first drying ventilation during which we compared the influence of three air velocities on the evolution of the water content of the grains and their temperature. The set velocities are: 0.10 m/s, 0.15 m/s and 0.24 m/s. Two other ventilations were carried out in October (2015) and in January (2016) with an air velocity of 0.24 m/s. The results obtained allowed us to conclude that the ventilation of the wheat is necessary as soon as it is put in the silo to cause its drying. On the other hand, it allows the heat generated and the cooling of the wheat to be evacuated in autumn and winter. Drying and cooling were carried out in successive layers before stabilizing. There is therefore a transfer of heat and humidity by forced convection.
Article
Keywords: Ventilation, forced convection, drying, cereals